5+3(4x+1)=

Simple and best practice solution for 5+3(4x+1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5+3(4x+1)= equation:


Simplifying
5 + 3(4x + 1) = 0

Reorder the terms:
5 + 3(1 + 4x) = 0
5 + (1 * 3 + 4x * 3) = 0
5 + (3 + 12x) = 0

Combine like terms: 5 + 3 = 8
8 + 12x = 0

Solving
8 + 12x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + 12x = 0 + -8

Combine like terms: 8 + -8 = 0
0 + 12x = 0 + -8
12x = 0 + -8

Combine like terms: 0 + -8 = -8
12x = -8

Divide each side by '12'.
x = -0.6666666667

Simplifying
x = -0.6666666667

See similar equations:

| 9x+3x=-3 | | 14lnx=20 | | 5n-12=108 | | 3(x^2-6)=129 | | -18=-6x-6 | | 4x+8=-2x+24 | | -7-6w+5+3= | | X^3lnx=0 | | x-.13x-58=75 | | 400=200+0.04s | | 7-9r+5r-8= | | 2(x-3)=3(x-2)+2 | | lnx^4=0 | | 3078x-4104=57(54x-72) | | 6m-2n=27 | | X/6-8=1 | | (3e+5f-7)+(4e-8f)= | | X^2-62=2x+1 | | F(x)=-2x^2+10x+48 | | -7(-3y+2)-4y=3(y-1)-5 | | -3(2x+8)=-66 | | x+4=7.8 | | 3(5x+4)=-5(2x-4) | | (-3/4)x(7/4) | | 9x+31x-10=8(5x+9) | | -5v+7=6(v+3) | | 2x-6=3x-6+2 | | 2(-6+5x+6xsquared)=0 | | -5(y-5)=3y-7 | | -3(4+6w)-4= | | -18-10x=-16x+18 | | 189-10x=3x+20 |

Equations solver categories